2012
DOI: 10.1111/1471-0528.12040
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of pregnancies in women with cystic fibrosis—single centre experience 1998–2011

Abstract: Objective To describe the maternal and fetal outcomes of pregnancies in women with cystic fibrosis.Design Retrospective study.Setting Single obstetric hospital and adult cystic fibrosis centre.Methods Retrospective case-note review of pregnant women with cystic fibrosis referred for antenatal care and delivery.Main outcome measures Maternal and fetal outcomes, mode of delivery, lung function and pregnancy complications.Results Forty-eight pregnancies were studied in 41 women. There were two miscarriages, 44 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
4
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 29 publications
8
73
4
9
Order By: Relevance
“…21 We reported high rates of preterm (46.7%) and CS (46.15%) deliveries. This is in keeping with data from most other studies, 11,12 although differs from a recent report from Burden et al 21 of 100% vaginal deliveries, reflecting the multifactorial indications for CS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…21 We reported high rates of preterm (46.7%) and CS (46.15%) deliveries. This is in keeping with data from most other studies, 11,12 although differs from a recent report from Burden et al 21 of 100% vaginal deliveries, reflecting the multifactorial indications for CS.…”
Section: Discussionsupporting
confidence: 88%
“…8 Poor lung function is commonly cited as the most significant single predictor of maternal morbidity, prematurity and fetal complications. [11][12][13][14][15][16][17][18][19][20] Pregnancy is not recommended in significant lung disease (forced expiratory volume in one second (FEV1) 550% predicted) with a low body mass index (BMI), whilst cor pulmonale and pulmonary hypertension are considered absolute contraindications. 6,8,11 Current understanding and antenatal counseling is limited by a paucity of published series.…”
Section: Introductionmentioning
confidence: 99%
“…18,22,23,28,29 Increased rates of low birth weight (52.5 kg) have been reported in some studies but not all. 18,22,23,28 For most infants, Apgar scores will be normal, 29 rates of congenital malformations do not appear to be increased and perinatal death is rare.…”
Section: Impact Of Cf On Short-term Fetal Outcomesmentioning
confidence: 97%
“…18,22,23,28 For most infants, Apgar scores will be normal, 29 rates of congenital malformations do not appear to be increased and perinatal death is rare. 12,18,22,23,28,29 Short-term neurological and cognitive development appears to be normal, although subtle sequelae of CF pregnancy on the child have not been comprehensively studied to date. 22 …”
Section: Impact Of Cf On Short-term Fetal Outcomesmentioning
confidence: 99%
“…Case reports and epidemiological studies showed that the A. OVERVIEW OF NUTRITION AND DIETS IN CYSTIC FIBROSIS long-term outcome of women with CF who become pregnant was not worse than that of CF women who did not become pregnant [2,[10][11][12][13][14][15]. Case reports and epidemiological studies showed that the A. OVERVIEW OF NUTRITION AND DIETS IN CYSTIC FIBROSIS long-term outcome of women with CF who become pregnant was not worse than that of CF women who did not become pregnant [2,[10][11][12][13][14][15].…”
Section: Historical Perspectivementioning
confidence: 99%